Distance estimating algorithm based on gradient neighbors in wireless sensor networks - ZHENG Ming-cai1; 3; ZHANG Da-fang1; 2 (Tongxin xuebao)
A modified distance-estimating algorithm DV-GNN was presented to improve the precision of indirect dis- tance measuring in wireless sensor networks, theoretical basis was analyzed, and implementing process was given. With the help of gradient neighbors, the resolving power of distance estimating was increased from effective radio range to the distance interval between nodes. Compared with the algorithm DV-hop, under the preservation of the low cost and over- head, the measuring accuracy was improved largely. The analysis and simulation validated that the method was quite ef- fective in wireless sensor networks with dense nodes.